2020
DOI: 10.5230/jgc.2020.20.e13
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Efficacy of S-1 Monotherapy or Capecitabine Plus Oxaliplatin as Adjuvant Chemotherapy for Patients with Stage II or III Gastric Cancer after Curative Gastrectomy: a Propensity Score-Matched Multicenter Cohort Study

Abstract: Purpose: To compare long-term disease-free survival (DFS) between patients receiving tegafur/gimeracil/oteracil (S-1) or capecitabine plus oxaliplatin (CAPOX) adjuvant chemotherapy (AC) for gastric cancer (GC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 15 publications
1
24
4
Order By: Relevance
“…The researchers found that pathologic T and N stages and completion of planned chemotherapy were prognostic factors for recurrence. 20 Although there was a significant difference in OS between XELOX and TS-1 groups of stage II patients in our cohort, there was no significant difference in stages IIIA-IIIC, and no significant difference in DFS was found between the 2 groups at any stage.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The researchers found that pathologic T and N stages and completion of planned chemotherapy were prognostic factors for recurrence. 20 Although there was a significant difference in OS between XELOX and TS-1 groups of stage II patients in our cohort, there was no significant difference in stages IIIA-IIIC, and no significant difference in DFS was found between the 2 groups at any stage.…”
Section: Discussioncontrasting
confidence: 56%
“…The researchers found that pathologic T and N stages and completion of planned chemotherapy were prognostic factors for recurrence. 20 Although there was a significant difference in OS between XELOX and TS-1 groups of stage II patients in our cohort, there was no significant difference in stages IIIA-IIIC, and no significant difference in DFS was found between the 2 groups at any stage. These survival discrepancies among previous studies might be due to different AJCC stages (seventh or eighth), treatment compliance of patients, slight differences in planned adjuvant chemotherapy completion rates, dose reduction, and duration of chemotherapy.…”
Section: Discussioncontrasting
confidence: 56%
“…Among these, we excluded 6741 studies since they were reviews, books, or meta-analyses, and we included 11,880 clinical trials and randomized controlled studies. Based on the titles and abstracts of the 11,875 studies, five clinical studies comparing S-1 versus CAPOX as AC in patients undergoing gastrectomy were selected [ 14 , 15 , 16 , 17 , 18 ]. Two of these studies were excluded because they collected data from a relatively short-term three-year follow-up after gastrectomy [ 14 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the studies comparing three-year postoperative survival, a multicenter propensity score matching (PSM) study showed that adjuvant CAPOX chemotherapy was more effective than S-1 for stage IIIB or IIIC gastric cancer [ 14 ]. On the other hand, among the studies analyzing five-year postoperative survival, two studies that conducted PSM showed comparable oncologic outcomes between the two regimens [ 15 , 16 ]. A single-center, observational study presented the potential for superior efficacy of the CAPOX regimen against stage II gastric cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the S-1 completion rate was higher than the CAPOX completion rate, although the difference was not statistically significant. AC compliance is a prognostic factor for recurrence [ 17 ]. An ACTS-GC trial post-hoc analysis showed that patients who completed AC had better survival than those who did not [ 18 ].…”
Section: Discussionmentioning
confidence: 99%